High pressure decontamination of building materials during radiological incident recovery. (November 2019) - Jolin, William C.; Magnuson, Matthew L.; Kaminski, Michael D.
Abstract: The release of radiological material from a nuclear incident has the potential to cause extensive radiological contamination requiring rapid decontamination. A promising method for rapid remediation is the use of pressure washers to decontaminate building and street surfaces. Pressure washers utilize both physical removal through surface ablation and chemical removal through desorption of bonded radionuclides. To understand the extent that each removal mechanism is present, overall removals, depth profiles, and wash water were analyzed from the pressure washing of various surfaces contaminated with cesium, strontium, and europium. Removals were dependent on surface type with over 80% of the radionuclides removed from concrete, 50–80% from asphalt, and only 20–25% from brick. Generally, the closer the radionuclide was to the surface of the material, the higher the removal, with europium being removed most readily followed by cesium then strontium, though some exceptions were evident. Comparing these removals and depth profiles of radionuclides in non-decontaminated coupons revealed that cesium and europium are mostly removed through surface ablation. Strontium, on the other hand, is desorbed from the surface, especially from brick and asphalt surfaces. Correspondingly, cesium and europium were attached to the particulates that were likely removed with the pressurized water. Strontium was primarily dissolved in the wash water, supporting the observation that the radionuclide is desorbed from each surface. Finally, the faster the surfaces were brought through the high pressure spray, the lower the removals, arising from decreases in both the physical and desorption mechanisms. Pressure washers were concluded to be a promising decontamination method during radiological incident relief. However, the surface and radionuclide identity must be considered when developing proper procedures. Graphical abstract: Image 1 Highlights: A pressure washer decontaminated asphalt, brick, and concrete surfaces contaminated with Cs-137, Sr-85, and Eu-152. The closer the radionuclide was to the surface of the material the higher the removal. Cesium and europium are mostly removed through surface ablation while strontium is chemically removed. The surface and radionuclide identity must be considered when developing proper procedures for using pressure washers.